The Implementation of Nature-based Learning Models to Improve Children's Motor Skills - Aulia Annisa; Panggung Sutapa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
The balance between fine and gross motor skills of children is important to be optimally stimulated. The purpose of this study was to determine the effectiveness of nature-based learning models in improving children's motor skills. This study used a quantitative method with a subject of 45 children aged 4-5 years in 3 kindergartens in Sleman Regency. The study design used one group pretest posttest with 3 treatments each. Data collection techniques using observations and interviews were analyzed using descriptive quantitative and the effectiveness was analyzed using the T test. The results showed that nature-based learning effectively increases motor skills because by using the five senses, children have learning experiences through play, according to age needs, using objects concrete, up to challenging activities. Nature-based learning model can be an innovation that can be used as material for further research related to cognitive, language, art, and social emotional in children